Effects of adiponectin extracts on blood parameters, histological & molecular changes in induced hyperglycaemic rats - Nuraniza binti Azahari (Kulliyyah of Allied Health Sciences,International Islamic University Malaysia, 2018)
Given the beneficial roles of adiponectin protein on body metabolism and its profound protective effects against metabolic diseases, a better understanding of the protein's secretion and regulation is very important. The objectives of this study were to extract, detect and quantify the total adiponectin in trimmed off abdominal adipose tissues from meat sources, namely chicken, beef and lamb, and test it on STZ-induced hyperglycaemic rats. Abdominal adipose tissues were isolated from the aforementioned sources and delipidation of the tissues were performed through chloroform/methanol extractions. Afterwards, the protein concentration was determined by using Protein Assay Bicinchoninate Kit method. This was followed by quantification of the adiponectin using ELISA assay kit. Followed by tests in STZ-induced hyperglycaemic rats on blood glucose and blood lipid, hormone measurement and lastly quantification of PPAR-α mRNA, AMPK mRNA, AdipoR1 mRNA, AdipoR2 mRNA and AdipoQ mRNA in the hepatocytes. The experiment was conducted in triplicates and the results were presented as mean ± SD. The data was statistically analyzed by using SPSS statistical software version IBM 21.0. One-way analysis of variance (ANOVA) was used and the data were considered statistically different at 95% confidence interval. Results indicated that the extraction of 10-gram subcutaneous adipose tissues from chicken, beef and lamb yielded 0.10-gram, 0.15 gram and 0.15 gram of protein, respectively, which were 1 - 1.5 % from the total tissue mass. The protein concentration in the abdominal adipose tissues from chicken, beef and lamb were 1.25 ± 0.05, 1.75 ± 0.05 & 2.53 ± 0.07 mg/ml, respectively. The isolated adiponectin concentration in chicken, beef and lamb was 158 ± 0.05 ng/ml, 24240 ± 0.05 ng/ml and 37 ± 0.08 ng/ml, respectively. Adiponectin concentration in beef abdominal adipose tissues was significantly (p<0.001) higher compared to chicken and lamb. In the animal study, the normal, insulin-treated, PCCA-treated (protein containing chicken adiponectin), PCBA-treated (protein containing beef adiponectin) and PCLA-treated (protein containing lamb adiponectin) hyperglycaemic groups exhibited significantly (p<0.05) reduced blood glucose levels after the treatment period when compared with the NT (control diabetic) group. Similarly, the normal, insulin-treated, PCBA-treated and PCLA-treated diabetic groups exhibited significantly (p<0.05) reduced in blood cholesterol and triglycerides levels after the treatment period when compared to the NT group. Moreover, serum adiponectin concentration was significantly (p<0.05) higher in the normal, insulin-treated, PCBA-treated, PCCA-treated and PCLA-treated diabetic groups as compared to the NT group. Nevertheless, serum insulin concentration was significantly (p<0.05) higher in the normal, insulin-treated and PCBA-treated groups as compared to the NT group. Lastly, AMPK, AdipoR1 and AdipoR2 mRNAs were significantly (p<0.05) upregulated in the normal, insulin-treated, PCBA-treated, PCCA-treated and PCLA-treated diabetic groups as compared to the NT group. However, there was no significant difference among groups for PPAR-α mRNA and AdipoQ mRNA. In conclusion, the present study suggested that the beef protein had the highest amount of adiponectin protein and gave the highest positive effects on STZ-induced hyperglycaemic rats. Thus, adiponectin proteins extracted from these cheaper sources of wasted adipose tissues in meat can be one of the promising target for future novel pharmacological and therapeutic treatments/preventions for insulin resistance and metabolic diseases.